ANALYSIS OF DIGITAL SKILL CONFIRMATION FACTORS IN THE USE OF MOBILE BANKING SERVICES IN BOGOR REGENCY - Rafid Maulana Akbar; Refi Rifaldi Windya Giri (Jurnal Ekonomi, 2023)
This research was conducted to confirm what digital skills factors could represent the construct, at least one that represented the use of mobile banking services in Bogor Regency. This research uses non-probability sampling and purposive sampling techniques and the number of samples used is 366 who are banking customers who use mobile banking in Bogor Regency. In this study, the analysis technique used Confirmatory Factor Analysis (CFA) and by using AMOS software version 24 as a tool for conducting analysis in the research conducted. The research variables used in this study include operational mobile skills, information navigation skills, creative skills, and social skills with a total of 30 indicators used. The results obtained based on digital skills factor analysis on the use of mobile banking services in Bogor Regency show that all the indicators used in this study represent the construct because the loading factor value is more than > 0.30 which is stated to be valid but the fit model in this study is still found to be a model that does not fit , so that the modification of the model is carried out to get a fit model. This research is a form of researcher's contribution to confirm what factors influence digital skills in the use of mobile banking services then suggestions that can be given for further research using exploratory factor analysis (EFA) so that the model to be used gets a fit model when reprocessed using confirmatory factor analysis (CFA).